Harnessing multi source point cloud technology to overcome high resolution building information modeling of Manganti Dam, Indonesia : a preliminary result - Hendriatiningsih, Sadikin; Widyastuti, Ratri; Saptari, Asep Yusup; Harpiandi, Andri; Suhandri, Hendy F.; Nasradeen A. Khalifa (Penerbit Universiti Kebangsaan Malaysia, 2021)
Building Information Modelling (BIM) is a technology involving the generation and management of digital information of physical and functional characteristics of places (in 2D or 3D), which is developed to obtain built assets, planning, construction maintenance and operation, and construction management system. This case study is BIM development for the Manganti dam, located in Central Java, Indonesia. The dam itself is a vital irrigation system and is located in an earthquake-prone area, which makes significant risk factors for the surrounding environment. Therefore, continuous monitoring for the dam should be taken seriously into action by acquiring accurate information. Supporting that purpose, the spatial information of the dam, in 3D form, should be accurately presented in the mapping process. Although the Terrestrial Laser Scanner (TLS) is well known for providing accurate geometry information, its information detail is still limited to an accessible area. Consequently, it creates gaps in shadow areas which possibly can be compensated by the data from Handheld Laser Scanner (HLS). In this contribution, we are focusing on analyzing the reliability of TLS and HLS combination for high-resolution mapping and, possibly, high accuracy mapping. The geometric accuracy of the 3D model is comparing the dimension of the model to the dimension measurement by the Electronic Total Station (ETS) measurement.